1955
DOI: 10.1097/00000658-195510000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Primary Peptic Ulcerations of the Jejunum Associated with Islet Cell Tumors of the Pancreas

Abstract: Fortunate indeed is the surgical service that does not have one or more problem cases of recurrent marginal ulceration despite the adequacy of the surgical attack. These un fortunate few not only harass the individual surgeon but tend to humble those who ad vocate a so-called ideal surgical procedure for the control of the acid-peptic factor. On rare occasions repeated gastric resections, At the time this paper was published, Drs. Zol linger and Ellison were affiliated with the De partment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
147
1
5

Year Published

1960
1960
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,185 publications
(155 citation statements)
references
References 7 publications
2
147
1
5
Order By: Relevance
“…Gastrinoma or Zollinger-Ellison syndrome was first reported as a tumor and a syndrome in human medicine in 1955 [10]. Gastrinoma is a malignant endocrine tumor, that is mainly characterized by hypersecretion of gastrin derived from D cells in pancreatic Langerhans islets [1,3,6].…”
mentioning
confidence: 99%
“…Gastrinoma or Zollinger-Ellison syndrome was first reported as a tumor and a syndrome in human medicine in 1955 [10]. Gastrinoma is a malignant endocrine tumor, that is mainly characterized by hypersecretion of gastrin derived from D cells in pancreatic Langerhans islets [1,3,6].…”
mentioning
confidence: 99%
“…The families concerned had had a double social disturbance in that their family ties had been severed and they were also subject to the restricting environment of life in a flat, and it is suggested that in view of the large number of flats which are being built, and the tendency towards family mobility, further investigation is needed into the effects of flat life on Y., 1967, 4, 386-390 Hypersecretion of gastrin by an islet cell tumour of the pancreas is believed to be the cause of the Zollinger-Ellison syndrome (Zollinger and Ellison, 1955; Gregory, Tracy, French, and Sircus, 1960). Patients with this condition have extreme gastric hypersecretion and peptic ulceration.…”
mentioning
confidence: 99%
“…med. Y., 1967, 4, 386-390 Hypersecretion of gastrin by an islet cell tumour of the pancreas is believed to be the cause of the Zollinger-Ellison syndrome (Zollinger and Ellison, 1955;Gregory, Tracy, French, and Sircus, 1960). Patients with this condition have extreme gastric hypersecretion and peptic ulceration.…”
mentioning
confidence: 99%
“…Consequently, based on a high serum gastrin level as well as clinical signs and immunohistological findings, we diagnosed the disease as canine gastrinoma, a rare tumor of the pancreas. Originally described by Zollinger and Ellison and known as the cause of Zollinger and Ellison syndrome in humans [16], gastrinoma is a gastrin-secreting neoplasm of the pancreatic cells. This disease is characterized by a gastrointestinal ulcer and erosion as a consequence of hypersecretion of gastric acid from the parietal cells of the stomach wall stimulated by hypergastrinemia [14].…”
Section: )mentioning
confidence: 99%
“…In the original report on the subject, gastrinoma is described as a gastrin-secreting tumor originating in the pancreatic islet cells [16]. Normally, in adults, gastrin is secreted from the duodenum and gastric pylorus, not from the pancreas [13].…”
Section: )mentioning
confidence: 99%